THE EFFECTIVENESS OF VIDEO AND STORYBOOK EDUCATION ON THE LEVEL OF KNOWLEDGE ABOUT RABIES DISEASE IN STUDENTS OF ESCOLA BÁSICA FILIAL (EBF) CATOLICA DE NOSSA SENHORA DE FATIMA PADIAE TURMA 6, MUNICIPIU REGIAO ADMINISTRATIVA SPPECIAL OECUSSEAMBENO, TIMOR L - Adelino Nuno Da Conceição; Rahaju Ningtyas; Maria Emilia Tresna Lengari (Jurnal Kesehatan Karya Husada, 2025)
ABSTRACT Introduction: Rabies is a zoonotic disease that can be transmitted through the bite or scratch of an infected animal and almost always leads to death if not promptly treated. The rapid spread of rabies in Timor Leste, particularly in Oe-Cusse, highlights the importance of increasing public knowledge, especially among students, to prevent its spread. Video-based education and storybooks are considered efective in conveying health information to students who frequently interact with pets. This study aims to evaluate the efectiveness of these twoeducational media in improving students ' knowledge of rabies at Escola Básica Filial (EBF) Católica de Nossa Senhora de Fátima Padiae, Oe-Cusse Ambeno, Timor Leste. Methods This study uses a pre-test and post-test design with a single group ofparticipants consisting of 50 sixth- grade students at EBF Católica de Nossa Senhora de Fátima Padiae. Before receiving video-based education and storybook-based education, students took a pre-test toassess their knowledge of rabies. Subsequently, students were educated using two mediamethods: a 20-minute educational video and a storybook focused on rabies prevention. The students then took a post-test to measure the change in their knowledge. The WilcoxonSigned-Ranks test was used to analyze the significant difference between pre-test and posttest scores. Results The results showed that before the education, 50% of the students had high knowledge regarding rabies. However, after receiving video and storybook-based education, 74% of the students demonstrated a significant improvement in knowledge. Statistical analysis using the Wilcoxon Signed- Ranks test resulted in a p-value of 0.000, which is smaller than 0.05,indicating that the difference between the pre-test and post-test is statistically significant.This suggests that both educational methods were efective in improving students' knowledge about rabies. Discussion Video-based education and storybooks were proven efective in improving students ' knowledge about rabies at Escola Básica Filial (EBF) Católica de Nossa Senhora de FátimaPadiae, Oe-Cusse Ambeno, Timor Leste. The video, with dynamic visualizations, helped students understand complex concepts such as the symptoms, transmission, andprevention of rabies. Meanwhile, the storybook provided an emotional narrative approach, helping students connect with the topic through easily understandable stories. Although a small number of students showed no significant change, the majority demonstrated clear improvements in knowledge, indicating the efectiveness of both methods. Therefore, both media can serve as efective alternatives for health education in areas with a high prevalence of rabies. Further research is needed to evaluate the long-term impact of this education and to develop other more interactive methods. Keywords : Rabies, health education, educational video, educational storybook, student knowledge